PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, JUMLAH KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP PRAKTIK MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013-2015) - Monika, Planeta (Jurnal Ilmiah Mahasiswa FEB, 2017)
Manajerial ownership, institusional ownership, board of commisioner, and audit committee existence are elements of good corporate governance. Good Corporate Governance is needed in for the company to have advanced aspects of transparency, independence, accountability, responsibility, and fairness of the actions taken by management to raise or lower the gain in earnings management practices. The aim of this study is to examine the impact of independent variabel such as manajerial ownership, institusional ownership, the number of independent board of commissioners, and audit committee on dependent variabel earnings management practices by using multiple and simple linear regression method to gain the related coeficients. This study uses 63 sample manufacture financial statement from 2013 until 2015 enlist in BEI. The result from this study shows that there are negative significant  independent variable such as manajerialownership and the number of board of independent commissioner with dependent variable on earnings management. However, both of the institusional ownership and the number of Audit Commitee are  insignificant with earnings management. Subsequently,  The data result shows that independent variable such as manajerialownership, institusional ownership, the number of board of independent commissioner and the number of Audit Commitee are  insignificant with earnings management by using multiple linear regression.  Keywords : earnings management, manajerial ownership, institusional ownership, the number of board independent of  commisioner, and the number of audit committee.